Shared Attention. (September 2015) - Shteynberg, Garriy
Shared attention is extremely common. In stadiums, public squares, and private living rooms, people attend to the world with others. Humans do so across all sensory modalities—sharing the sights, sounds, tastes, smells, and textures of everyday life with one another. The potential for attending with others has grown considerably with the emergence of mass media technologies, which allow for the sharing of attention in the absence of physical co-presence. In the last several years, studies have begun to outline the conditions under which attending together is consequential for human memory, motivation, judgment, emotion, and behavior. Here, I advance a psychological theory of shared attention, defining its properties as a mental state and outlining its cognitive, affective, and behavioral consequences. I review empirical findings that are uniquely predicted by shared-attention theory and discuss the possibility of integrating shared-attention, social-facilitation, and social-loafing perspectives. Finally, I reflect on what shared-attention theory implies for living in the digital world.